The template synthesis, characterization, and thermal investigation of new Heterocyclic binucleating Schiff base complexes - Sönmez, M; Sekerci, M (Taylor & Francis Inc, 2004)
1-Amino-5-benzoyl-4-phenyl-1H-pyrimidine-2-one (L'H-2) reacts with benzil (LO-2) and salts Cu(AcO)(2) . H2O, NiCl2 . 6H(2)O, CO(ACO)(2) . 4H(2)O, CdCl2 . 2H(2)O in 2: 1 : 2 molar ratio in n-butanol to give several solid complexes of the general composition [(M)(2)(L')(2)(L)(X)(4)] . nH(2)O. The precursor and the metal complexes of the Schiff base have been characterized by elemental analyses, molar conductances, IR spectra, electronic, and thermal studies.
Keywords: template synthesis; acyclic; Heterocyclic Schiff base